Irish local and artisan foods: Multiples make space! - Michelle Dunne; Angela Wright (Cogent Business & Management, 2017)
Consumers are increasingly discerning about food choices. This research explores the attitudes of Irish consumers to local and artisan food products, and, in particular, if they would consider the supermarket environment as a location of choice for the purchase of these foods. This research applied a quantitative methodology to address the research question. 126,110 supermarket customers were contacted through an Irish supermarket loyalty data base, which resulted in 14,646 completed responses. This rich data allowed the researchers access to the attitude of Ireland's consumers to speciality local food products, normally absent from the supermarket shelf. 98.8% of respondents would like to be able to purchase local food products in a supermarket, and 76% of respondents expect to pay either less than, or the same price for local food products, as they do for other similar standard foods. This research will be of direct benefit to parties involved with the grocery retail sector in Ireland.
Keywords: 650